Bilateral angular carpal deformity in a dog with craniomandibular osteopathy - Pettitt, R.; Fox, R.; Comerford, E. J.; Newitt, A. (Veterinary and Comparative Orthopaedics and Traumatology, 2012)
A four-month-old West Highland White Terrier was presented to the Small Animal Teaching Hospital at the University of Liverpool with the complaint of a bilateral angular carpal deformity. A 20° valgus deformity was present in both thoracic limbs, centred on the distal radial physes. Both distal ulnas were grossly thickened and there was concomitant thickening of the rostral mandible and calvarium. The dog exhibited signs of resentment on palpation of the mandible and signs of pain were elicited on flexion and extension of both elbow joints. No signs of pain were evident on palpation of the ulnas or calvarium. Radiographic images of both ulnas showed marked amorphous periosteal new bone formation. The distal ulnar physes were closed centrally and both elbow joints had humeroulnar subluxation. Radiographic changes to the calvarium and mandibular rami were consistent with a diagnosis of craniomandibular osteopathy. A bilateral ulna ostectomy was performed to correct the angular limb deformity and elbow subluxations. Histology of the ostectomised pieces showed changes consistent with craniomandibular osteopathy.
Keywords: Craniomandibular osteopathy; angular limb deformity; growth deformities